Industrial Water Pollution in Savar Upazila: A Geospatial Approach to Ecological Sustainability - Hossain, S. M. Nawshad; Abedin, A.B.M. Siddiqul; Mahmud, Md. Munir (The Jahangirnagar Review, 2024)
Industrialization is crucial for economic growth and societal advancement, with nearly 50% of Bangladesh's population engaged in agriculture. However, this rapid industrialization has led to uncontrolled urbanization, environmental alterations, and illegal riverbank development. One of the gravest threats is the discharge of industrial effluents into natural hydrological systems, causing adverse effects on human health and aquatic ecosystems. This study examines the escalating pollution of rivers surrounding Savar Upazila due to swift industrialization. Dhalweshari, Turag, and Bangshi rivers are suffering from severe contamination, with high levels of cadmium, lead, and chromium in their water and sediment. The study uses a review-based approach to address the complex interplay of industrial activities, river water quality, and broader environmental and human health concerns. Data is collected from diverse sources, including organizational reports, journals, articles, and newspapers. Advanced tools like ArcGIS 10.8 and "Google Earth-pro" are used to assess pollution dispersion patterns. To mitigate industrial pollution, the study suggests establishing an independent Environmental Impact Assessment (EIA) review board, making the EIA review and reports publicly accessible, and third-party verification and public disclosure of post-development environmental monitoring. Mitigation strategies include policy intervention, management practices, technical solutions, and raising awareness among stakeholders. Implementing these measures can enhance environmental performance and promote sustainable solutions towards environmental preservation in the face of rapid industrialization.